Ethnobotanical study of medicinal plants used by the inhabitants of the village of Genoy, Municipality of Pasto, Colombia - Felipe Angulo, Andrés; Rosero, Ricardo; González Insuasti, Martha Sofía (Universidad y Salud, 2012)
Between October 2011 and January 2012 an ethnobotanical study focused on the knowledge of ethnobotanical species used for ethnobotanical purposes, as well as the cultural relationship around the use of those species by the inhabitants of Genoy Township located in San Juan de Pasto, Nariño was carried out. 38 people were interviewed using a semi-structured survey: 27 women and 11 men of whom 4 were key sources of information. All the participants were randomly selected. The relative importance of medicinal species (RIE) was estimated, as well as other etnobotanical indices that allowed calculating the value of recognition of use for each species (RUV). As a result, information for 63 medicinal species was recorded and distributed in 31 botanical families and 56 genres. The most important families, in order, were: Lamiaceae, Asteraceae and Apiaceae. The most used parts of the plant were leaves (89.47%) and flowers (21.05%). A greater number of the species were used to treat gastrointestinal, reproductive, skin and respiratory disorders. The following medicinal plants that are widely used by local people showed the highest RIE and RUV values: cedron (Aloysia citriodora), chamomile (Matricaria chamomilla) and oregano (Origanum vulgare).